Respuesta :
Answer:
In mixed number format: 6 1/2
Step-by-step explanation:
To solve the following equation: 7(x - 2) = 3(x + 4), first we need to apply the distributive property:
7(x - 2) = 3(x + 4) → 7x -14 = 3x + 12
Solving for 'x' → 4x = 26 → x = 6.5
→ In mixed number format: 6 1/2
For this case we must solve the following equation:
[tex]7 (x-2) = 3 (x + 4)[/tex]
Applying distributive property to the terms within the parenthesis we have:
[tex]7x-14 = 3x + 12[/tex]
We subtract 3x on both sides of the equation:
[tex]7x-3x-14 = 12\\4x-14 = 12[/tex]
Adding 14 to both sides of the equation:
[tex]4x = 12 + 14\\4x = 26[/tex]
Dividing between 4 on both sides of the equation:
[tex]x = \frac {26} {4} = \frac {13} {2}[/tex]
ANswer:
[tex]x = \frac {13} {2}\\x = 6 \frac {1} {2}[/tex]